(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2021)
This text was written with the aim of stimulating reflections on the trajectory of Grande Otelo, considering the social and artistic context of the period in which he lived and reflecting on issues that determined the way he developed his career. For this contextualization, aspects of her trajectory that coincide with characteristics of the careers of other artists in the popular scene in the period, in theater and in the circus were addressed, such as work since childhood, specialization of performance and aesthetic choices guided by constant care in please the public.